Rancang Bangun Aplikasi Augmented Reality Pembelajaran Tata Surya Berbasis Android - Septo Distiano Rifky; Selfi Artika (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The need for interactive media in learning is increasingly in demand by the public in line with the development of smartphones as a basic necessity in this day and age. Augmented Reality (AR) is a technology that can be used in children's learning process in recognizing the planets in the Solar System. The use of Augmented Reality in the learning process can also handle the problems of current traditional learning media that are less informative. This research aims to help learning by directly visualizing 3D objects of solar system objects, which can cause curiosity in students so that students can start to be more active in learning. The research method used the waterfall method which is divided into several stages including requirements analysis, system design & design, implementation, and testing, and operation & maintenance. This augmented reality interactive learning application uses markerless augmented reality media to interact with users using a camera and is made using Unity and Vuforia software. This research results in implementing an interactive 3D augmented reality learning application for the android-based solar system. With this application, it is expected to improve the quality of learning and can help students learn the solar system better.